Unintended Pregnancy among Pregnant Women in Ghana: Prevalence and Predictors - Samuel H. Nyarko (Hindawi Limited, 2019)
Background. Unintended pregnancy is seen as the key concept for better understanding the fertility and the unmet need for family planning of populations. It is seen as a major challenge among women in many developing countries including Ghana. However, there is scarcely nationally representative information on its prevalence and predictors in Ghana. Methods. In a cross-sectional study design, data for this study were extracted from the 2014 Ghana Demographic and Health Survey. The prevalence of unintended pregnancies was computed, and logit regression models were fitted to predict the factors influencing unintended pregnancies in the country. Results. The total prevalence of unintended pregnancies among pregnant women in Ghana was found to be 40%. Background characteristics such as age (OR=4.85, CI=1.48-15.84), level of education (OR=0.50, CI=0.26-1.01), marital status (OR=3.83, CI=1.67-8.75), parity (OR=0.13, CI=0.05-0.32), and region of residence (OR=0.11, CI=0.03-0.31) were the significant predictors of unintended pregnancy, net of unmet need for contraception. However, unmet need for contraception (OR=7.13, CI=1.57-8.91) serves as an independently significant predictor of unintended pregnancy regardless of the background characteristics of respondents. Conclusions. The study findings strongly underscore the need for significant improvement in the access to contraception methods and family planning information in the quest to considerably reduce unintended pregnancies in the entire country.